2017
DOI: 10.1158/1078-0432.ccr-16-2796
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I–II Study of the Oral PARP Inhibitor Rucaparib in Patients with Germline BRCA1/2-Mutated Ovarian Carcinoma or Other Solid Tumors

Abstract: Purpose: Rucaparib is a potent, oral, small-molecule PARP inhibitor. This phase I-II study was the first to evaluate singleagent oral rucaparib at multiple doses.Experimental Design: Part 1 (phase I) sought to determine the MTD, recommended phase II dose (RP2D), and pharmacokinetics of oral rucaparib administered in 21-day continuous cycles in patients with advanced solid tumors. Part 2A (phase II) enrolled patients with platinum-sensitive, high-grade ovarian carcinoma (HGOC) associated with a germline BRCA1/2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
161
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 218 publications
(172 citation statements)
references
References 42 publications
11
161
0
Order By: Relevance
“…As reported in previous studies of rucaparib and other PARP inhibitors, 5, 6, 9, 10, 11 gastrointestinal side-effects, asthenia or fatigue, and myelosuppression were common treatment-emergent adverse events in the rucaparib group. Management of adverse events included supportive care and dose modifications (including treatment interruption or dose reduction).…”
Section: Discussionsupporting
confidence: 74%
“…As reported in previous studies of rucaparib and other PARP inhibitors, 5, 6, 9, 10, 11 gastrointestinal side-effects, asthenia or fatigue, and myelosuppression were common treatment-emergent adverse events in the rucaparib group. Management of adverse events included supportive care and dose modifications (including treatment interruption or dose reduction).…”
Section: Discussionsupporting
confidence: 74%
“…FDA approval of rucaparib (Clovis Oncology) was announced on December 19, 2016 based on the results of two multicenter randomized open label trials, Study 10 and ARIEL, parts 1 and 2 [18, 19]. The two phase (I/II) Study 10, reported in early 2017, enrolled 56 patients with g BRCA mutated platinum sensitive ovarian cancer with two to four lines of previous therapy.…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…The two phase (I/II) Study 10, reported in early 2017, enrolled 56 patients with g BRCA mutated platinum sensitive ovarian cancer with two to four lines of previous therapy. The phase II portion of Study 10 enrolled 42 patients, after establishing the phase I dose of 600 mg twice daily, and showed a 59.5% investigator-assessed overall response rate [18]. ARIEL 2 enrolled patients with g BRCA mutations and platinum-sensitive high grade ovarian carcinoma, and defined HR deficiency subgroups: BRCA mutant (deleterious germline or somatic), BRCA wild type with loss of heterozygosity (LOH) high, or BRCA wildtype with LOH low, using a cutoff of 14% or more genomic LOH for LOH high.…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…17,18 In this study, we assessed the efficacy and safety of rucaparib monotherapy in patients with locally advanced or metastatic PC with a known deleterious BRCA1/2 mutation.…”
Section: Introductionmentioning
confidence: 99%